Mitigation of voltage sag caused by unbalanced load by using dft controlled dvr - Soomro, Dur Muhammad; Wei Keat, Yew; Baloch, Mazhar Hussain; Abdullah, Mohd Noor; Mohammad Radzi, Nur Hanis; Ahmed Memon, Zubair
This paper describes the source of voltage sag occurring in the power system. Voltage sag can occur in the system by means of having line faulty, inrush current drawn by loads and switching operation. However, the unbalanced load in the system causing voltage sag is studied here. In this paper, the pattern of voltage sag caused by balanced three phase (3Ø) and unbalanced single phase (1Ø) loads are studied and compared. The percentage of voltage sag caused by both cases are calculated using voltage sag calculation formulae by keeping definition values of sag between 10% - 90% as stated in IEEE Std. 1159-2009. While the percentage of voltage unbalance in the system caused by 1Ø unbalanced loads is calculated by using voltage unbalance formulae. The philosophy of voltage sag mitigation is studied by using a proposed mitigation device after studied the causes of voltage sag. There are several researches that have been done by proposing different kind of devices. The Dynamic Voltage Restorer (DVR) is one of the most cost-effective methods to protect the sensitive loads in the system for mitigating the voltage sag. The voltage sag is mitigated by injecting voltage dynamically to compensate the voltage differences between normal input supply and disturbed output supply. In order to achieve the voltage injection into the system dynamically to mitigate voltage sag, a control technique has to be applied on the DVR. There are many control techniques which are applied on the DVR to mitigate the voltage sag, such as the Direct-Quadrature-Zero (dq0), Fuzzy Logic (FL) and Space Vector Pulse Width Modulation (SVPWM). The Discrete Fourier Transform (DFT) is one of the control techniques which is implemented on the DVR in this paper. The modeling and simulation results of the DFT controlled DVR were carried out by using MATLAB/Simulink to validity the performance of the sag mitigation. As a result, the DFT controlled DVR was successfully designed and 100% mitigated the voltage sag both with balanced and unbalanced loads in the system.